1959
DOI: 10.1111/j.1365-2494.1959.tb01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Ear‐bearing Capacity of Tillers Arising at Different Times in Herbage Grasses Grown for Seed

Abstract: Three experiments are described, two with S215 meadow fescue and one with S37 cocksfoot, all grown for seed, during which all new tillers, soon after their appearance, were labelled at intervals of a month—a total of nearly 12,000 tillers. Whatever the first date of observation, the earliest tillers were always found to have contributed the largest proportion of the ears present at harvest. In one experiment applied nitrogen caused an increase in the number of tillers and ears, without however affecting the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1963
1963
1996
1996

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…Because of the high contribution of earlyformed tillers to the seedhead population (following sowing and seed harvest) efforts should be made to encourage the production of high tillernumbers during the post-harvest and autumn period. The present results support findings of other workers with perennial ryegrass (20); timothy (8,21); Bromus inermis (7); prairie grass (20) and cocksfoot (5,12).…”
Section: Tiller Survivalsupporting
confidence: 95%
See 1 more Smart Citation
“…Because of the high contribution of earlyformed tillers to the seedhead population (following sowing and seed harvest) efforts should be made to encourage the production of high tillernumbers during the post-harvest and autumn period. The present results support findings of other workers with perennial ryegrass (20); timothy (8,21); Bromus inermis (7); prairie grass (20) and cocksfoot (5,12).…”
Section: Tiller Survivalsupporting
confidence: 95%
“…This effect is apprently inherent in the organization of the plant since it occurs irrespective of the time of sowing (12). However, any discussion ofdecreasing ear-bearing capacity with later tiller formation must take into account that this is not solely an age effect.…”
Section: Seedhead Populationmentioning
confidence: 98%
“…Nitrogen application generally decreases tiller mortality of widely spaced plants ( Wilson, 1959) but in dense populations of grasses grown for seed production nitrogen application seldom influences the proportion of dead tillers (Langer and Lambert, 1959;Hill and Watkin, 1975;Hebbiethwaite, 1977). High nutrient encourages vigorous growth of the sward often leading to an almost completely closed canopy (Brougham, 1958;Robson, 1973) and as spring advances improvement in the light level above the sward is paralleled by a deterioration of the light level deep in the sward.…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that the increased proportion of tillers in the older categories in the S treatment populations caused a shift towards earlier flowering. It has long been known that the oldest tillers within the tiller population of a grass sward contribute the largest proportion of flowering tiller (Langer & Lambert, 1959;Hill & Watkin, 1975). Hill & Watkin (1975) also demonstrated that management, in their case grazing v. no grazing, can cause a shift towards higher numbers of early-emerging flower heads, but this is the first study to demonstrate long-term effects of spring grazing management on flowering in the following year.…”
Section: Long-term Effectsmentioning
confidence: 94%